STATISTICAL MODELING OF TEST ANXIETY AMONG THE STUDENTS OF FACULTY OF NUMERICAL AND PHYSICAL SCIENCES UNIVERSITY OF PESHAWAR - Qamruz Zaman, Bilal Ahmad, Kiran Ali, Habib Shah, Danish Wasim, Meerullah, Sidra Nawaz, Aizaz Shah (International Journal of Contemporary Issues in Social Sciences, 2024)
The present research is based on examining the exam Anxiety factors among the BS students of the faculty of numerical and physical science, University of Peshawar. A well-structured questionnaire was distributed among the BS student at the University of Peshawar. A sample of 250 students was selected. The data were analyzed by using SPSS 23.0 version. The frequency of male respondents was 125 and female respondents were 125. 174 students were settled in the university hostels and 76 were day scholars. Majority of the parents were illiterate. More than 60% of the students belonged to the rural area and belonged to the average income family. One of the main reasons of the students suffering from exam anxiety was their family history of anxiety. A lower grade in the last exam was also a reason of anxiety. Round about 68% of the students are not able to manage the time for study. Another reasons included absentees from school, memorizing the lessons without understanding the themes. Majority of students were of the opinion that the lack of preparation for the exam is the main reason of anxiety during the exam. Nearly 66.40% of the students were scared about the result and 33.60% of the students were free from this fear. There is no significant association between Gender and any other related factor.